Diffuse Pruritic Papular and Nodular Skin Eruption in a Febrile Farmer: A Quiz - Mattia Fabio Molle; Astrid Herzum; Emanuele Cozzani; Marco Mora; Aurora Parodi (Medical Journals Sweden, 2022)
Abstract is missing (Quiz)